(untitled) (Annals of Bangladesh Agriculture, 2023)
Onion is a major spice crop that is grown and consumed extensively in Bangladesh and across the world. The present study was carried out with the goal of analyzing the growth and trend of area, production and yield of onion in Bangladesh. Annual area, production, and yield data of onion in Bangladesh were collected from FAOSTAT for 50 years from 1970 to 2019. The semi-log model and compound growth model were used to investigate the growth of onion whereas exponential trend model was employed to estimate the trend of area, production, and yield of onion in Bangladesh. According to the growth rate and trend line estimates, the area under the onion crop has been augmented over time. Specifically, the semi-log model findings show that the onion area, production and yield grew by on an average 3.87%, 5.46% and 1.58% per year, respectively. The compound annual growth rate estimate indicated significant growth of onion area, production and yield from 2015 to 2019. The exponential trend line for onion area, production and yield showed slow growth rate from 1970 to 1990 but relatively faster growth later on. These evaluations may aid the government in balancing demand and supply, as well as in regulating the price of onion in local markets Bangladesh. Ann. Bangladesh Agric. 27(2):201-210